Typography Meets Sustainability: A Case Study of Pedagogical Design Innovation for Climate Advocacy and Cultural Identity - Georges, Hala (Harmonia: Journal of Arts Research and Education, 2025)
This article explores the integration of typography in promoting sustainability through a qualitative case study of the TYPO-COP28 initiative conducted at the University of Sharjah’s Visual Communication department in 2023. This study examines how typography can function as an active, participatory tool for sustainability advocacy within educational settings. Through structured research-based pedagogical methods, 16 undergraduate students created typographic designs addressing environmental and cultural sustainability themes, demonstrating that well-designed pedagogical frameworks enable emerging designers to contribute meaningfully to environmental discourse. Analysis of student designs revealed primary thematic approaches: renewable energy integration (75%), cultural heritage bridging (68%), and material sustainability consciousness (100%). Audience reception data demonstrated high impact, with 82% perceiving designs as effective climate communication and 65% sharing designs on social media. The pedagogical framework generated significant learning outcomes, including increasing conceptual sophistication and internalization of environmental responsibility as a core design principle. This research provides an evidence-based framework for integrating sustainability and design activism into visual communication education.